Against Harmful Research on Non-Agreeing Children - Chwang, Eric (Bioethics, 2015)
The Code of Federal Regulations permits harmful research on children who have not agreed to participate, but I will argue that it should be no more permissive of harmful research on such children than of harmful research on adults who have not agreed to participate. Of course, the Code permits harmful research on adults. Such research is not morally problematic, however, because adults must agree to participate. And, of course, the Code also permits beneficial research on children without needing their explicit agreement. This sort of research is also not problematic, this time because paternalism towards children may be justifiable. The moral problem at the center of this paper arises from the combination of two potential properties of pediatric research, first that it might be harmful and second that its subjects might not agree to participate. In Section 2 of this article I explain how the Code permits harmful research on non-agreeing children. Section 3 contains my argument that we should no more permit harmful research on non-agreeing children than on non-agreeing adults. In Section 4, I argue that my thesis does not presuppose that pediatric assent has the same moral force that adult consent does. In Section 5, I argue that the distinction between non-voluntary and involuntary research is irrelevant to my thesis. In Section 6, I rebut an objection based on the power of parental permission. In Section 7 I suggest how the Code of Federal Regulations might be changed.